The Securitization of Energy Issues from The Perspective of Security Studies - Ramadhan, Iqbal (Indonesian Journal of Energy, 2023)
Security studies debated the phenomenon of "high politics," such as politics and the military, at the outset of their development. As the study's object, it discusses the arms race, nuclear war, and political coups. Following the end of the Cold War, the economic, social, and environmental sectors became subjects of study in security studies. Not only that, but security studies also address issues that are frequently overlooked, such as energy issues. This is undeniably one of the most pressing issues in security studies today. The energy issue discusses how the country's foreign policy efforts will be carried out in order to avoid the threat of domestic energy scarcity. The inclusion of energy issues in security studies does not happen overnight. Through this scientific article, the author intends to examine how energy issues can become part of security issues. The author employs the concept of securitization to examine the securitization of energy issues from the standpoint of a security study. The author used a qualitative method in this study, with secondary data collection (journals and archive documents) as part of the data collection technique. The discussion of this scientific article has resulted in the securitization of energy issues being divided into three stages. Non-securitization, politicization, and securitization are the stages. Energy issues are not considered security issues during the non-securitization stage. When the energy issue becomes politicized, it poses a real threat that the government must address. Meanwhile, security issues have defined threats in the securitization stage. However, this securitization process will only take place if the audience accepts the threat and the state takes responsibility for mitigation efforts. The author comes to the conclusion that the securitization of energy issues is mutual between the state and the audience (society).